2015
DOI: 10.1051/ps/2015012
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian sequential testing of the drift of a Brownian motion

Abstract: We study a classical Bayesian statistics problem of sequentially testing the sign of the drift of an arithmetic Brownian motion with the 0-1 loss function and a constant cost of observation per unit of time for general prior distributions. The statistical problem is reformulated as an optimal stopping problem with the current conditional probability that the drift is non-negative as the underlying process. The volatility of this conditional probability process is shown to be non-increasing in time, which enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Note that this is not a new approach in these kinds of problems, but corresponds to standard methodology in filtering theory, see Bain and Crisan (2009, Section 3.3). For example, Ekström and Vaicenavicius (2015) make use of essentially the same technique when analysing a sequential testing problem of the drift of a Brownian motion. If a change of measure is defined via…”
Section: Bayesian Formulation With General Prior Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that this is not a new approach in these kinds of problems, but corresponds to standard methodology in filtering theory, see Bain and Crisan (2009, Section 3.3). For example, Ekström and Vaicenavicius (2015) make use of essentially the same technique when analysing a sequential testing problem of the drift of a Brownian motion. If a change of measure is defined via…”
Section: Bayesian Formulation With General Prior Distributionsmentioning
confidence: 99%
“…Now, our interest here is not in providing the precise technical conditions under which a solution may be obtained via the free-boundary method and integral equations. Detailed discussions are provided for a long list of similar problems elsewhere in the literature, see Peškir and Shiryaev (2006) for an overview or Ekström and Vaicenavicius (2015) for a more recent result. Rather, we wish to illustrate how the general approach may be used to solve Anscombe's classical problem and various extensions of it.…”
Section: Symmetric Priorsmentioning
confidence: 99%
“…set-ups where the unknown parameters can take only two possible values. In [23], a hypothesis testing problem for a case with three possible drifts is examined, and in [10] a composite hypothesis problem for the drift of a Wiener process is studied with a general prior distribution. Moreover, [9] study a sequential estimation problem for a Wiener process in the same set-up.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, [9] study a sequential estimation problem for a Wiener process in the same set-up. Key to the analysis in [10] and [9] is the choice of appropriate variables. In fact, in [10] it is shown that if instead of the observation process one uses the conditional probability Π as state variable, then the corresponding continuation region is shrinking in time; a similar result holds for sequential least-square estimation if one uses the conditional expectation as state variable.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the connection between optimal stopping problems and free-boundary problems, Shiryaev (1969Shiryaev ( , 1978 provides an explicit solution of the hypothesis testing problem when the dri can take only two di erent values. Notable recent contributions include the extension to the nite horizon hypothesis testing problem (Gapeev and Peskir, 2004), the characterization of the solution to the original Cherno problem in terms of an associated integral equation (Zhitlukhin and Muravlev, 2013), a study of the case with three hypotheses (Zhitlukhin and Shiryaev, 2011), and a study of the case with general prior distributions (Ekström and Vaicenavicius, 2015). Along a related line of research, various authors have extended the problem to include more general underlying processes.…”
Section: Introductionmentioning
confidence: 99%